Sacramental Efficacy in Karl Rahner and Cognitive Linguistics - Schlesinger, Eugene R. (Philosophy & theology, 2013)
An examination of Rahner’s theology and cognitive linguistics shows that the two are basically in accord concerning sacramental efficacy. This article also puts cognitive linguistics into conversation with Rahner’s theologies of expression. In Rahner’s theology of the symbol, he argues that all beings express themselves in that which is not themselves. Furthermore, Rahner noted the existence of uniquely powerful “primordial words” (Urworte), which mediate the reality to which they point. Cognitive linguistics sees all human knowing as mediated by the “embodied mind,” and characterized by concept integration, wherein a given thing comes to be known in terms of another. This understanding of embodied mind, poses a significant challenge to the Christian tradition. This challenge is answered, though, by Rahner’s distinctive anthropology and christology.